Assessment of students, knowledge regarding AIDS in Medical Technical Institute in Erbil City - Nazar Ali Sheren; Radhwan Hussein Ibrahim; Kareem F.Aziz Al-Barzingy (Kufa Journal for Nursing Sciences)
Background: The acquired Immunodeficiency Syndrome (AIDS) is one of the most common health problems of 21st century and has been pandemic disease that threats the world population .Since AIDS was recognized as distinct new disease entity in (1981), nearly 60 million individuals worldwide have been infected by HIV, of those more than 90% were in developing world . According to international statistic Iraq is still among the low prevalence continues for AIDS.